Incidence, clinical impact and treatment outcomes of valve thrombosis after transcatheter mitral valve implantation. (25th November 2020) - Kikoine, J; Urena, M; Brochet, E; Nguyen, C; Carrasco, J.L; Ducrocq, G; Fuchs, A; Vahanian, A; Iung, B; Himbert, D
Abstract: Background: Transcatheter mitral valve implantation (TMVI) is a new treatment option for high-risk surgical patients with degenerated bioprosthesis (ViV), failed annuloplasty rings (ViR) and severe mitral annular calcification (ViMAC). However, limited data exist on transcatheter heart valve thrombosis. Purpose: The aim of this study was to report the incidence, clinical impact and treatment outcomes of transcatheter heart valve (THV) thrombosis in patients undergoing TMVI. Methods: All consecutive patients undergoing TMVI in our center between July 2010 and September 2019 were included. A transoesophageal echocardiography and a computed tomography (CT) were performed before hospital discharge and at each clinical visit, at 3 months, at 1 year and yearly after. THV thrombosis was defined as the presence of at least one thickened leaflet with restricted motion suggestive of thrombus confirmed by TOE and/or contrast CT. All patients received anticoagulation therapy with vitamin K antagonists (VKA) and a low dose of aspirin for the first 3 months. Results: A total of 132 patients underwent TMVI (62 ViV, 36 ViR and 34 ViMAC). Among them, 16 (12.1%) patients had a THV thrombosis. Median age was 67 years old and 56.2% of patients were women. Median time to diagnosis of THV thrombosis was 78 days. Early THV thrombosis was observed in 7 (43.7%) and in 13 (81.2%) patients THV thrombosis occurred within the first 6 months after the procedure. 8 out 9 patients with subacute or late THV thrombosis were not anticoagulated or with subtherapeutic anticoagulation. No stroke or thromboembolic events occurred in these patients. No change in mitral gradient was observed in 14 out 16 patients. VKA were indicated in all patients. THV thrombosis resolved in all but one patient. Conclusion: THV thrombosis is frequent after TMVI, occurs mainly within the first 6-months after the procedure, are mostly subclinical and resolves after optimization of anticoagulation treatment. An anticoagulation therapy for at least 6 months may be necessary. Funding Acknowledgement: Type of funding source: None